MANAJEMEN PENDIDIKAN MUHAMMADIYAH: SINERGI NILAI ISLAM DAN PROFESIONALISME PENGELOLAAN PENDIDIKAN - Ulpah Maspupah,; Moh Roqib,; Siti Mutmainah,; Ngaliyah Dwi Lestari, (re-JIEM (Research Journal of Islamic Education Management), 2025)
Muhammadiyah education management integrates progressive Islamic values and modern management principles in managing educational institutions from elementary to tertiary level. Muhammadiyah is oriented not only toward academic achievement, but also toward the development of student’s character and faith. This study employs a literature review method by analyzing books, official documents, and journal articles relevant to Muhammadiyah education management. The review discusses philosophical foundations, organizational structure, management implementation, as well as challenges and innovations, including adaptation to technological developments and global dynamics. The findings indicate that Muhammadiyah education management is able to integrate Islamic values with professionalism, however, it still faces challenges related to the quality of human resources, quality standards, and the utilization of information technology. Therefore, strengthening management training and educational digitalization is recommended to ensure that Muhammadiyah educational institutions remain relevant and competitive in the future.